2014
DOI: 10.1177/0275074014524298
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Stressors and Health-Related Outcomes in Public Service

Abstract: While business and psychology researchers have strived to identify effective strategies to reduce occupational stress, public administration scholars have paid insufficient attention to this issue. This article examines the role of motivational bases in the stressor-wellbeing relationship, a nascent research area in business and psychology, focusing on a particular type of motivation that is salient in public organizations: public service motivation (PSM). Based on a survey of 412 police officers from a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 97 publications
(131 reference statements)
3
71
0
2
Order By: Relevance
“…Houston (2011) x Johnson (2012) x Kim (2012) x Kim et al (2013) x Kjeldsen (2012) x Kjeldsen (2014) x Liu and Tang (2011) x x x x Liu, Tang, and Zhu (2008) x Liu, Tang, and Yang (2013) x Liu, Yang, and Yu (2014) x Moynihan and Pandey (2007) x Pandey , Wright, and Moynihan (2008) x Park and Rainey (2008) x Perry (1996) x Perry (1997) x Petrovsky and Ritz (2013) x x Ritz (2009) x Steijn (2008) x Taylor (2008) x Taylor (2010) x x van Loon, Leisink, and Vandenabeele (2013) x x Vandenabeele (2008b) x Vandenabeele (2009) x Vandenabeele and Van de Walle (2008) x Ward (2014) x Wright, Moynihan, and Pandey (2012) x Wright and Pandey (2008) x Wright and Pandey (2011) x…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Houston (2011) x Johnson (2012) x Kim (2012) x Kim et al (2013) x Kjeldsen (2012) x Kjeldsen (2014) x Liu and Tang (2011) x x x x Liu, Tang, and Zhu (2008) x Liu, Tang, and Yang (2013) x Liu, Yang, and Yu (2014) x Moynihan and Pandey (2007) x Pandey , Wright, and Moynihan (2008) x Park and Rainey (2008) x Perry (1996) x Perry (1997) x Petrovsky and Ritz (2013) x x Ritz (2009) x Steijn (2008) x Taylor (2008) x Taylor (2010) x x van Loon, Leisink, and Vandenabeele (2013) x x Vandenabeele (2008b) x Vandenabeele (2009) x Vandenabeele and Van de Walle (2008) x Ward (2014) x Wright, Moynihan, and Pandey (2012) x Wright and Pandey (2008) x Wright and Pandey (2011) x…”
Section: Resultsmentioning
confidence: 99%
“…Other methods are identified. (2012) 3D 13i Andersen and Serritzlew (2012) 1D 4i Bellé (2013) x Brewer and Selden (1998) 1D 3i Brewer, Selden, and Facer (2000) 6D 40i Q-methodology Bright (2005) x Bright (2007) x Caillier (2013) x Caillier (2014) Christensen and Wright (2011) x Coursey, Yang, and Pandey (2012) x Desmarais and Gamassou (2014) x Giauque, Ritz, Varone, and AnderfuhrenBiget (2012) 4D 11i Houston (2011) 1D 2i Johnson (2012) 2D 7i Kim (2012) 4D 20i Kim et al (2013) x Kjeldsen (2012) 3D Semistructured Interview Kjeldsen (2014) 3D 11i Survey and interview Liu and Tang (2011) 3D 12i Liu, Tang, and Zhu (2008) x Liu, Tang, and Yang (2013) 3D 12i Liu, Yang, and Yu (2014) 4D 18i Moynihan and Pandey (2007) 2D 7i Pandey, Wright, and Moynihan (2008) x Park and Rainey (2008) 1D 6i Perry (1996) x Perry (1997) x Petrovsky and Ritz (2013) 4D 10i Ritz (2009) x 2D 5i Steijn (2008) 1D 1i Taylor (2008) 1D 2i Taylor (2010) 1D 5i van Loon, Leisink, and Vandenabeele (2013) 4D 15i Vandenabeele (2008b) 3D 13i Vandenabeele (2009) 5D 18i Vandenabeele and Van de Walle (2008) 3D 5i Ward (2014) 3D 13i Wright, Moynihan, and Pandey (2012) x Wright and Pandey (2008) x Wright and P...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bellé ; Houston ; Liu et al. ; van der Wal ). Such research has been conducted with good reason as PSM has been found to enhance work performance (Grant ; Ritz et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, Liu et al. () found that PSM can moderate the relationship between burnout‐related constructs such as work stressors and well‐being. However, as highlighted previously, PSM may also possess a dark side.…”
Section: Literature Reviewmentioning
confidence: 99%